Design of graded materials by particle reinforcement during accumulative roll bonding - Schmidt, Christian; Ruppert, Mathis; Höppel, Heinz Werner; Nachtrab, Frank; Dietrich, Anja; Hanke, Randolf; Göken, Mathias (Advanced Engineering Materials, 2012)
Graded distributions of copper particles in ultrafine-grained aluminium sheets are produced by accumulative roll bonding and particle reinforcement. The metallic copper particles are sprayed on the sheet surfaces under variation of spray distance and/or relative velocity of the spray gun to the sheet. Therewith, the particle content could be varied by a factor of three. After solutionizing, the successful gradation is clearly proven by tensile tests showing a steady and monotonous gradient along the rolling direction. By a systematic analysis of the spraying process, the particle content profile is calculated. Accuracy of the calculation is confirmed by electrical resistivity measurements. The presented method enables the production of tailored sheets by graded particle reinforcement. The graded sheets are also used for basic investigation of materials properties along graded compositions.
WW1::920